Optimization of ultrasound-assisted extraction of naturally occurring glucosinolates from by-products of Camelina sativa L. and their effect on human colorectal cancer cell line - Pagliari, Stefania; Giustra, Chiara Maria; Magoni, Chiara; Celano, Rita; Fusi, Paola; Forcella, Matilde; Sacco, Grazia; Panzeri, Davide; Campone, Luca; Labra, Massimo (Frontiers in Nutrition, 2022)
Food waste generated by small and medium agro-industrial enterprise require appropriate management and valorisation in order to decrease the environmental problems and recover high value products, respectively. In this study, the Camelina sativa seed by-product was used as source of glucosinolates. To begin, the chemical profile of the extract obtained using the ISO procedure was performed by UPLC-HRMS/MS analysis. In addition, an extraction method based on the ultrasound assisted extraction was developed as alternative and green method to recover glucosinolates. The main parameters that affect the extraction efficiency were optimized using a response surface design. Under the optimized conditions, the USA extract showed an improvement of the extraction yield with a reduction of organic solvent amount than those obtained using the ISO procedure. Finally, the USAE was purified and tested on human colorectal cancer cell lines showing promising results.